Analysis of a single-phase, quasi-halbach magnetised tubular permanent magnet motor with non-ferromagnetic support tube. - Ibrahim, Taib; Wang, Jiabin; Howe, Dave (2008)
The paper describes the analysis of a short stroke, single phase quasi-Halbach magnetised tubular permanent magnet linear motor with non- ferromagnetic tube. The open-circuit magnetic field distribution is established analytically in terms of a magnetic vector potential formulated in the cylindrical coordinate system. The analytical field solution allows the prediction of flux linkage, back-emf and thrust force of the linear motor in closed forms and facilitates design optimisation. The analytically results are validated by finite elements analyses. A prototype linear motor has been constructed and the static performance test has been carried out. The experimental results have validated the predictions. Performance comparison is also given with a design variant which employs a ferromagnetic supporting tube.